2020
DOI: 10.31577/sp.2020.01.790
|View full text |Cite
|
Sign up to set email alerts
|

The role of teacher support, students’ need satisfaction, and their psychological capital in enhancing students’ self-regulated learning

Abstract: Because self-regulated learners do better in university and tend to be successful students, many authors consider that the development of self-regulatory learning skills in students has to become a priority for higher education. The present study aimed to investigate the explanatory role of psychological capital, as a personal resource, over and above teacher support and needs satisfaction, in relation to students' preference for self-regulating their learning (i.e., using cognitive strategies and self-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
2
18
0
1
Order By: Relevance
“…The work-home enrichment model suggests that resources in the work domain can increase personal resources, which can be then utilized in the family domain [11,32]. Previous research has found that a higher level of psychological capital is associated with increased cognitive skills such as self-regulation [33] and improved work-family enrichment [54]. The observed association between psychological capital and family satisfaction may be explained by a work-home enrichment process in which resources generated by psychological capital (e.g., cognitive skills) in the work domain can be transferred to the family role.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The work-home enrichment model suggests that resources in the work domain can increase personal resources, which can be then utilized in the family domain [11,32]. Previous research has found that a higher level of psychological capital is associated with increased cognitive skills such as self-regulation [33] and improved work-family enrichment [54]. The observed association between psychological capital and family satisfaction may be explained by a work-home enrichment process in which resources generated by psychological capital (e.g., cognitive skills) in the work domain can be transferred to the family role.…”
Section: Discussionmentioning
confidence: 99%
“…According to the work-family enrichment model, psychological capital may mobilize other personal resources such as cognitive skills at work, which may, in turn, be transferred to the family domain and lead to an improvement in family satisfaction. Sava et al [33] found that psychological capital contributed to improved self-regulation, suggesting that psychological capital could mobilize cognitive skills that could be utilized in the family domain. On the other hand, a high level of psychological capital may enable individuals to marshal other resources to perform well at work, and therefore promote their positive effects, which, in turn, may improve their performance in the family domain and hence increase family satisfaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The theory of selfdetermination (Weinstein et al, 2011) also describes how managed self-control positively affects a person by making him or her more energetic when it comes to developing their capabilities. Also, self-control is considered as a psychological resource for the success of university education (Borzova & Mosunova, 2020;Sava et al, 2020) and further professional activity (Fomina et al, 2020;Halama, 2017;Pilotti et al, 2019).…”
Section: Research Questionsmentioning
confidence: 99%
“…The SDT postulates three basic psychological needs: the need for relatedness, the need for autonomy, and the need for competence (Deci & Ryan, 2000). The authors argue that psychological need fulfillment in a work environment is a personal resource because need satisfaction can be energizing and sustain human behaviors (Gagné & Deci, 2005; Sava, Vîrgă & Paloș, 2020), thus might be increasing organizational commitment.…”
Section: Introductionmentioning
confidence: 99%